Anticonvulsant and antioxidant activity of aqueous leaves extract of Desmodium triflorum in mice against pentylenetetrazole and maximal electroshock induced convulsion - Bhosle,Vaibhav (2013)
The present investigation was aimed to study an anticonvulsant activity of aqueous extract of Desmodium triflorum (L.) DC., Fabaceae, in mice. Animal models of epilepsy namely the pentylenetetrazole, and maximal electroshock induced convulsion were used to evaluate the anticonvulsant effects of the extracts. The biochemical estimation was done by measuring the lipid peroxidation and reduced glutathione. In the pentylenetetrazole induced convulsion, aqueous extract of D. triflorum 800 mg/kg significant delayed the onset of convulsion, reduced the duration of convulsion (p<0.05) and reduced mortality. The aqueous extract of D. triflorum 800 mg/kg dose reduced hind limb tonic extension phase of maximal electroshock induced convulsion induced convulsion in mice (p<0.05). The pretreated aqueous extract of D. triflorum showed significant inhibition of lipid peroxidation and increases the reduced glutathione level in mice brain tissue (p<0.001). The results revealed that D. triflorum possesses a significant dose dependent anticonvulsant activity.